UPAYA PEMERINTAH VIETNAM DALAM MENANGANI PERDAGANGAN MANUSIA WARGA NEGARA VIETNAM DI KAMBOJA PADA TAHUN 2020-2023 - Shabrina, Dini; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study analyzes Vietnam’s efforts to address human trafficking of its nationals in Cambodia from 2020 to 2023. The issues intensified during the COVID-19 pandemic, when China’s zero-COVID policy restricted cross-border trade, exacerbating poverty and unemployment among Vietnamese communities. These vulnerabilities were exploited by trafficking networks in Cambodia, leading to a surge in victims in 2022. In response, the Vietnamese government implemented measures focused on prevention, victim protection and international cooperation. This study employs a descriptive qualitative approach, utilizing the perspective of Liberalism and the theory of Multi-Track Diplomacy (MTD). The research relies on secondary data and highlights that the Vietnamese government’s efforts have involved multiple actors across different MTD tracks. Within this framework, the diplomacy applied encompasses Track One, Track Two, and Track Nine of Multi-Track Diplomacy. This study finds that the Government of Vietnam has pursued notable efforts to combat human trafficking of its nationals in Cambodia through diplomatic engagement with the Greater Mekong Subregion (GMS), UNODC, UN-ACT, and IOM under Track One of Multi-Track Diplomacy. Collaboration has also been established with the Blue Dragon Children’s Foundation under Track Two and the Pacific Links Foundation under Track Nine. Supplementary measures include policies and programs targeting trafficking prevention, poverty reduction, and victim support. However, these efforts have not been fully effective, as the Vietnamese government has not demonstrated substantial results in resolving the human trafficking cases documented during the period studied. Keyworrds: Vietnamese Government, Cambodia, Human Trafficking, Effort, Multi-Track Diplomacy